1995
DOI: 10.1111/j.1600-0773.1995.tb01017.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nicotine and Its Interaction with Carbon Tetrachloride in the Rat Liver

Abstract: In order to study the effects of nicotine on liver, groups of rats were given nicotine doses that simulated those seen in chronic smoking (54 and 108 mumol/l of nicotine) for 10 days. A subgroup was also given a single subcutaneous injection of 6 g/kg of carbon tetrachloride (CCl4) shortly before the animals of the group were killed. Histology demonstrated a significant hepatotoxic effect in the group receiving 108 mumol/l of nicotine when compared with the control group in the form of fatty change, focal or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 19 publications
(11 reference statements)
0
45
0
Order By: Relevance
“…[23][24][25] Smoking yields chemical substances with cytotoxic potentials. 26) In one puff of a cigarette, the smoker is exposed to more than 10 15 free radicals in the gas phase alone, with additional exposure in the tar phase equal to more than 10 17 free radicals per gram. 27,28) Cigarette smoke consists of many chemicals, including nicotine, tar with its many carcinogens, and gaseous compounds including carbon monoxide (CO).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] Smoking yields chemical substances with cytotoxic potentials. 26) In one puff of a cigarette, the smoker is exposed to more than 10 15 free radicals in the gas phase alone, with additional exposure in the tar phase equal to more than 10 17 free radicals per gram. 27,28) Cigarette smoke consists of many chemicals, including nicotine, tar with its many carcinogens, and gaseous compounds including carbon monoxide (CO).…”
Section: Discussionmentioning
confidence: 99%
“…25,48) Cigarette smoke contains a large number of chemical substances with hepatotoxic potential including nicotine. 26) Cigarette smoke also induces oxidative stress by stimulating NADPH oxidase and decreasing antioxidant defenses, leading to lipid peroxidation. 49) These effects could lead to increased hepatocellular damage and subsequent activation of resident hepatic stellate cells, a major fibrogenic celltype.…”
Section: Discussionmentioning
confidence: 99%
“…Data from experimental studies suggest that nicotine, a major component of tobacco smoke, was rapidly absorbed through the lungs and released into circulation. Thereafter, it is mainly metabolized through the liver inducing lesions characterized by steatosis and focal or confluent necrosis [19] . A recent study demonstrated that smoking was mainly related to increased inflammatory activity but not to the stage of fibrosis [20] , whereas Pessione et al [9] provided evidence that smoking could worsen the degree of fibrosis in CHC independent of other co-morbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…21 Seeing that the liver is the major site of nicotine metabolism, it has been considered highly susceptible for the oxidative stress associated with the toxicity of nicotine.In fact, many epidemiological studies have shown an association between smoking and accelerated progression of liver fibrosis in patients with a variety of chronic liver diseases such as primary biliary cirrhosis and chronic hepatitis C. 22,23 The experimental models of Azzalini et al 24 have shown that smoking caused oxidative stress and exacerbated the severity of nonalcoholic fatty liver disease in obese rats.Moreover, nicotine from heavy smoking increased the risk of developing hepatocellular carcinoma (HCC) 25,26 and liver cirrhosis. 27, 28 Yuen and colleagues 29 reported that nicotine administration at a concentration similar to those attained by cigarette smoking was hepatotoxic. 30 In this respect, Husain and coworkers demonstrated that ethanol supplementedto nicotine treatment might augment hepatotoxicity and oxidative damage in liver of nicotine treated rats.…”
Section: Introductionmentioning
confidence: 99%